Analysis the Yeast and Mold of Alcoholic Starter in the Production of Lao-Lao (Lao Whisky) from 6 Villages in Sayaboury District - BANDAVONG, Viraxay; CHANTHAKOUN, Vongpasith; KHOUNVILAY, Bounthieng; BOUNYAVONG, Teo (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
Local alcohol is a popular drink at various social events such as weddings, baci ceremony and festivals. This objective of this investigation was to study the use of starter cake in the production of local alcohol. Data related to starter cake were randomly collected in 6 villages (Ban Yai, Ban Nalao, Ban Simoungkhoun, Ban Simuang, Ban Thana and Ban Suan) in Sayaboury District, divided into 6 experiments collected from 6 villages to seek the moisture content (Mc), water activities (aw), pH, yeast and mold in starter cake through the use of standard protocol, PDA and YM BROTH by Spread plate method. The analysis was conducted on the date 1, 10, 20, and 30. The analysis was carried out. The results revealed that samples at date 1 of yeast has no statistically significant difference (p>0.05). However, at the date of 10, 20, 30 yeast of starter cake alcohol demonstrated statistically significant difference (p<0.05) as digest sugar turned to become alcohol. The amount of mold in 6 experiments of starter cake alcohol has statistically significant difference (p<0.05); in comparison with moisture, water activities, and pH, which has statistically significant difference (p<0.05). Therefore, yeast and mold are equivalent to the standard value of the production of starter cake of local alcohol. In summary, the results indicate that use of starter cake alcohol from 6 villages enable to produce local whisky.